The influence of the Covid-19 Pandemic on young online businesses - Nokya Suripto Putri (Universitas Airlangga, 2021)
Indonesia is one of the countries affected by the Covid-19 pandemic. The Covid-19 pandemic has a negative impact on economic, educational, socio-cultural, and other aspects. When viewed from a financial aspect, this pandemic has made efforts to shift trade from trading directly or face-to-face to online or commonly referred to as e-commerce, which is now an online business. This research method is quantitative and qualitative. Researchers used a purposive sampling technique to get respondents aged 15 to 25 who worked as online businesses during the Covid-19 pandemic. Then, the data analysis that the researchers did was descriptive statistical analysis. This study indicates that the most driving factor for young people aged 15 to 25 to do online business is to follow the current trends (37%). In addition, the inhibiting factor that many young people experience when running online businesses during the Covid-19 pandemic is a large number of competitors (37%). The number of competitors is related to the difficult economic situation during the Covid-19 pandemic. In addition, the results of this study also show that 60% of respondents choose that online business has no impact on academics because respondents say that doing business online provides positive energy. So, high school students, college students, and the general public (aged 18-25 years) can continue to develop online businesses even though they are during the Covid-19 pandemic.